2002
DOI: 10.1063/1.1431417
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the ion source extraction and low energy beam transport systems for the Spallation Neutron Source

Abstract: The ion source for the Spallation Neutron Source is a radio-frequency (rf) multi-cusp, volume-type H− source that is coupled to a rf quadrupole accelerator through a low energy beam transport (LEBT) system consisting of five electrostatic elements. To gain a deeper understanding of the operation of this system and to continue to refine the design, we have performed ion extraction and transport simulations using the computer code PBGUNS. A comparison is presented between simulation and the measured phase space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…A systematic study of outlet-aperture contours 15 indicated that a longer channel such as the one shown in Fig. 3, as opposed to the knife-edge shape seen in Fig.…”
Section: Beam Formationmentioning
confidence: 99%
“…A systematic study of outlet-aperture contours 15 indicated that a longer channel such as the one shown in Fig. 3, as opposed to the knife-edge shape seen in Fig.…”
Section: Beam Formationmentioning
confidence: 99%
“…A systematic study of outlet-aperture contours 16 indicated that a longer channel such as the one shown in Fig. 3, as opposed to the knife-edge shape seen in Fig.…”
Section: Beam Formationmentioning
confidence: 99%
“…A drawing of the new ion source is shown in Figure 6. Details of the extraction geometry and magnetic fields were optimized through the respective use of the software PBGUNS [11] and Infolytica [12] MagNet. In comparison to the current ion source, the new version has several improvements including: i) better coupling to the magnesium-vapor charge-exchange canal, ii) improved control of the magnetic field (by using a solenoid magnet rather than permanent magnets), iii) improved alignment capability, iv) the ability to operate at potentials higher than 30 kV, v) the elimination of internal water seals with O-rings, and vi) the use of commercially available brazed insulators (as opposed to a glued ceramic/metal extraction column).…”
Section: Future Improvementsmentioning
confidence: 99%